Hydrological Shifts Threaten Water Resources. Issue 8 (22nd August 2022) - Fowler, Keirnan; Peel, Murray; Saft, Margarita; Nathan, Rory; Horne, Avril; Wilby, Robert; McCutcheon, Connor; Peterson, Tim
Abstract: Recent shifts in the hydrological behavior of natural watersheds suggest acute challenges for water planning under climate change. Usually triggered by a multi‐year drought, these shifts involve a tendency for less annual streamflow for a given annual precipitation, and this behavior has now been reported on multiple continents. Future drying under climate change may induce similar unexpected hydrological responses, and this commentary discusses the implications for water planning and management. Commonly used hydrological models poorly represent these shifts in behavior and cannot be relied upon to anticipate future changes. Thus, their use may result in underestimation of hydroclimatic risk and exposure to "surprise" reductions in water supply, relative to projections. The onus is now on hydrologists to determine the underlying causes of shifting behavior and incorporate more dynamic realism into operational models. Key Points: Drought‐induced hydrological shifts toward less streamflow for a given precipitation amount have been reported across multiple continents Future drying under climate change may induce similar hydrological shifts Such responses add uncertainty to runoff projections, with the potential for "surprise" reductions in future streamflow